Treatment and control of blood pressure in Welsh patients with and without depression: A study of whole-population electronic health records - Elizabeth A. Ellins; Richard Summers; Carla White; Ann John; David P.J. Osborn; Keith Lloyd; Ashley Akbari; Michael B. Gravenor; Julian P. Halcox (PLoS ONE, 2025)
Background To explore differences in blood pressure treatment and control in patients with and without depression and a diagnosis of hypertension (HTN). Also to examine the possible impact of sex, socio-economic status (deprivation) and location of residence on any differences. Methods A retrospective observational cohort study (2010–2019) using individual level linked anonymised routinely-collected electronic health record (EHR) data sources was carried out. Patients with a prior or new diagnosis of hypertension, with and without depression were included. Outcome variables were prescription of antihypertensive therapy (AHT) within one year of entering the study for prior HTN or post for new HTN and documentation of blood pressure <140/90 mmHg. Logistic regression was used to explore the association between depression and outcome variables adjusting for sex, age group, deprivation, location of residence and other risk factors. Results Depression was associated with higher likelihood of AHT prescription in both prior (OR 1.71 95%CI 1.64–1.78 p < 0.001) and new HTN patients (OR 2.67 95%CI 2.38–3.00 p < 0.001). Similarly, depression was associated with successful blood pressure control in both prior (OR 1.42 95%CI 1.37–1.46 p < 0.001) and new HTN (OR 1.23 95%CI 1.08–1.40 p < 0.001). Females were less likely to be prescribed AHT than males, mainly driven by non-depressed females in both HTN groups. Depressed females were the most likely to have controlled blood pressure in both HTN groups. Conclusion Patients with depression are more likely to be prescribed AHT and have documented blood pressure control. Sex differences existed in treatment and control, indicating opportunities for potential improvements in these areas.